The detoxification of Cr(VI) by methanogens during the fermentation of environmentally hazardous Solidago canadensis plant - Kyrylov, S.K.; Bida, I.O.; Havryliuk, O.A.; Hovorukha, V.M.; Tashyriev, O.B. (Problems of Environmental Biotechnology, 2023)
The possibility of the effective detoxification of toxic chromium simultaneously with methanogenic fermentation of S. canadensis biomass was experimentally confirmed. The obtained results are promising for the development of environmental and energy biotechnologies.